La villa gallo-romaine d’Entre Deux Cours à Laquenexy (Moselle) : bilan de trois opérations de fouille préventive et d’une campagne de prospection géophysique - Gaël Brkojewitsch; Sébastien Jeandemange; Guillaume Asselin; Valentina Bellavia; Pierre Caillat; Amélie Corsiez; Laurent Forelle; Sophie Galland; Linda Herveux; Marc Leroy; Sandrine Marquié; Paul Merluzzo; et al. (Gallia)
Three rescue excavations conducted in the years between 2007 and 2012, covering a total surface of 17 790 m2, and a campaign of geophysical prospection conducted in 2014 (total surface investigated: 20 000 m2) allowed to investigate extensively the archaeological remains of a Roman villa at the locality Entre Deux Cours, municipality of Laquenexy (Moselle, Lorraine, France). While the rescue excavations focused principally on the remains of the pars rustica, the geophysical prospection made it possible to investigate the maximal extension of the villa and to obtain first results concerning the features and architectural organization of the pars urbana. The architectural plan of the villa is well-fitting into the established typology of the villae of northeastern Gaule: the villa of Laquenexy belongs to the type of the villae “à pavillons multiples alignés” (villae of axial organisation, characterized by opposite rows of annexe buildings surrounding the central courtyard of the pars rustica). The agricultural part of the villa complex is characterized by five buildings constructed on stone foundations, but there have been also some wooden, probably timber-framed buildings, and, furthermore, the excavation revealed several postholes, hearths and ditches. These remains are characterizing this extended villa and agricultural exploitation, covering a total surface of about 4 hectares. Several features (circular oven constructions with straight fireying pit and corn drying kiln are indicating the importance of cereal production within the agricultural economy of the Gallo-Roman site. Archaeobotanical analysis has revealed valuable information concerning the agricultural activities and cereal production. The archaeological finds unearthed during the different excavations (iron tools, small metal objects, stone-made objects) have been studied extensively. This focus of the archaeological research enables us to characterize the find assemblage. Furthermore, a paleo-metallurgical study of slags has delivered remarkable results concerning activities like blacksmithing and metalworking. Stratigraphic information confronted with the results of the find analysis (ceramics, coins…) and two radiocarbon dates enable us to fix the chronological time frame of the Gallo-Roman occupation between the 1st and the 4th c. AD.